Sistem Akses Masuk Perpustakaan Menggunakan Sistem Pengenalan Wajah dan Pengukuran Suhu Tubuh Berbasis Single Board Computer (Studi Kasus Perpustakaan Unand) - Shalsabilla Syaqila; Dodon Yendri (CHIPSET, 2022)
The library is one of the facilities used as a place to obtain information, improve literacy, and develop knowledge and insight. The level of security that is still lacking causes the high threat of crime caused and the spread of the virus which is still difficult to control, so this research was carried out by forming a system that could facilitate entry with facial recognition and body temperature measurement to improve the security system and be able to suppress the spread of the virus.The system will open a portal for entry access when the face image is recognized with a normal body temperature without any physical contact, while when the face is not recognized the system will provide a notification that the detected face image is not recognized.